Myasthenia gravis, castleman disease, pemphigus, and anti‐phospholipid syndrome. Issue 3 (6th February 2013) - Jakubíková, Michala; Piťha, Jiří; Latta, Jan; Ehler, Edvard; Schutzner, Jan
<x xml:space="preserve">Abstract</x> Introduction: Myasthenia gravis is an autoimmune disease marked by neuromuscular transmission failure at the neuromuscular junction. Castleman disease is a rare lymphoproliferative disease characterized by non‐cancerous angiofolicular hyperplasia of lymphatic tissue. Methods and results: We describe a young man with rapid, successive manifestations of myasthenia gravis, a solitary form of Castleman disease, pemphigus vulgaris, and anti‐phospholipid syndrome, which resulted in 2 ischemic cerebrovascular events that caused a severe central neurological deficit. Discussion: We were unable to find a similar case in the literature, but we hypothesize that the temporal concidence of these clinical entities may be related to a common immunological pathway, such as B‐cell activation. Therefore, we treated the patient with an immunosuppressant and anticoagulant treatment, as well as rituximab, a monoclonal antibody therapy against CD20+. Muscle Nerve 47:447‐451, 2013